The Reliability Research of DF-D2D Underlaying Cellular Networks - HUAN, C.; LIU, C. (Advances in Electrical and Computer Engineering, 2014)
In this paper, we propose a novel Device-to-Device (D2D) communication model, i.e., DF-D2D where the D2D communication is aided by a relay using the decode-and-forward (DF) strategy. Based on this model, we firstly analyze the outage probability and thereby obtain its exact expression. Then, we compare this probability with that of D2D. Finally, we obtain a threshold in which the reliability of DF-D2D is better than that of D2D based on the distances between different DF-D2D users. Analysis and simulation results show that DF-D2D could dramatically improve the reliability of conventional D2D systems when the location of the relay user changes within the threshold.